A meta-analysis to observe silage microbiome differentiated by the use of inoculant and type of raw material - Ridwan, Roni; Abdelbagi, Mohammed; Sofyan, Ahmad; Fidriyanto, Rusli; Astuti, Wulansih D.; Fitri, Ainissya; Sholikin, Mohammad M.; Rohmatussolihat,; Sarwono, Ki A.; Jayanegara, Anuraga; Widyastuti, Yantyati (Frontiers in Microbiology, 2023)
Silage fermentation is naturally carried out by lactic acid bacteria (LAB) to produce mainly lactic acid (LA) and other organic acids as preservatives. Along with fermentation time, the growth of LAB will replace and suppress undesirable microorganisms. This meta-analysis study aimed to explore the effects of LAB inoculants on microbial communities of silages differentiated by raw materials. A total of 37 papers with 185 studies and 475 datasets was used for building up the meta-database. Data were subjected to the mixed model methodology. Parameters observed were silage quality and the composition of bacterial communities in the silage post ensiling process. Results revealed that, four bacterial phyla with Weissella being dominated post ensiling process. Adding lactic acid inoculants in the silage has increased the abundance of Lactobacillus spp. and decreased significantly the Shannon index. Moreover, both L. plantarum and L. buchneri were increased, and subsequently Weissella, Pseudomonas, Proteobacteria, pH value, ammoniacal nitrogen (NH3-N), coliforms, and the yeasts were decreased significantly due the addition of LAB in the silage (p<0.05). However, the dry matter, LA, acetic acid (AA), ratio of LA to AA, and the LAB population were enhanced significantly (p<0.05). Among the LAB types, the lowest abundance of Pseudomonas was due to with LAB group, while the lowest abundance of Weissella and Proteobacteria was due to the addition of the combined LAB group. In conclusion, the addition of LAB is effectively enhancing bacterial communities and silage quality by altering bacterial diversity and the metabolic products of the silage materials as safe preservation.